Epidemiological profile and effectiveness of immediate postpartum contraception in Brazilian women - Steiner, Marcelo Luis; Mendes, Julia Lorenzini; Strufaldi, Rodolfo; Carneiro, Monica; Giovanelli, Silvana Aparecida; da Silva, Mariliza Henrique (Frontiers in Global Women's Health, 2023)
PURPOSE: The introduction of a contraceptive method (MAC) at the time of admission for childbirth care proves to be a window of opportunity to reduce unwanted pregnancies. METHODS: We analyzed the epidemiological profile of women who inserted copper intrauterine device (Cu-IUD), subdermal etonogestrel implant (ENG), tubal ligation (TL), depot medroxyprogesterone acetate (DMPA) or did not choose a contraceptive method (NCM) in the immediate postpartum. Also, we compared the contraceptive effectiveness of Cu-IUD and DPMA with non-MAC. RESULTS: Data from 20896 women were collected, of which 8183 (39%) opted for Cu-IUD, 559 (2.5%) DPMA, and 10989 (52.5%) for any method. When comparing these groups, women in the DPMA were younger (26.5±7.3, p<0.05), and NCM showed women with a lower number of pregnancies (2.2±1.3, p<0.05). Subjects in the TL group (4,6%) had the higher number of pregnancies (3,8±1.2, p<0.05), and ENG group, the highest number of miscarriages (1.6±1.3, p<0.05). Of those women who returned pregnant, 5.5% belonged to the DPMA group, 6% to the NCM group, and 2.3% to the Cu-IUD. CONCLUSIONS: Women who opted for Cu-IUD insertion were younger, had more pregnancies and vaginal delivery when compared to those who did not choose a method. Of those women who returned, the minority opted for Cu-IUD compared to those that opted for DPMA or no method